Specificity of Varenicline in Blocking Mesolimbic Circuit Activation to Natural and Drug Rewards. (10th February 2022) - Goldstein, Nitsan; Carty, Jamie R.E.; Betley, J. Nicholas
Highlights: Dopamine sensing reveals time-dependent effects of varenicline. Varenicline blocks nicotine-evoked dopamine signaling in dorsal and ventral striatum. Varenicline transiently elevates dopamine levels as a nicotine substitute. Varenicline slightly prolongs dopamine release evoked by other drugs. Varenicline does not influence the dopamine response to natural rewards. Abstract: The mesolimbic dopamine (DA) system reinforces behaviors that are critical for survival. However, drug dependence can occur when drugs of abuse, such as nicotine, highjack this reinforcement system. Pharmacologically targeting the DA system to selectively block drug reinforcement requires a detailed understanding of the neural circuits and molecular pathways that lead to the reward-based activation of mesolimbic circuits. Varenicline is an approved smoking cessation drug that has been shown to block nicotine-evoked DA increases in the nucleus accumbens (NAc) through action on nicotinic acetylcholine receptors. Because these receptors have been implicated in the reinforcement of other addictive substances, we explored the possibility that varenicline could broadly affect reward processing. We used in vivo fiber photometry to monitor midbrain DA neuron activity and striatal DA levels following either natural or drug rewards in mice treated with varenicline. We demonstrate that varenicline pretreatment enhances the suppression of nicotine-evoked DA release by attenuating DA neuron activity in the VTA. Varenicline's ability to attenuate DA release is highly specific to nicotine, and varenicline slightly elevates DA release when co-administered with morphine or ethanol. Furthermore, varenicline has no effect on DA release in response to naturally rewarding behavior such as food intake or exercise. These results demonstrate the exquisite specificity with which varenicline blocks nicotine reward and highlight the complexity with which different rewards activate the mesolimbic DA system.